Efektivitas Proses Pelapisan Amilum Terhadap Biochar Sekam Padi Dengan Pupuk NPK - Niis Atang, Utari Adriana; Iskandar , Taufik; Abrina Anggraini , Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Biochar is black charcoal rich in the element carbon (C) produced by the thermal decomposition of biomass at a relative temperature below 700Â°C without or with little oxygen, in a process called pyrolysis. Biochar can be used as an alternative soil repairer. In this research, biochar and NPK will be mixed because NPK is a fertilizer that contains complete nutrients. The aim of this research is to determine the effectiveness of biochar (pukchar) and NPK fertilizers coated with starch by using the coating method for agriculture. The coating is one of the materials that serve to coat and protect the particles of substances in the raw material, protecting the material from oxygen, moisture, and light. The variables used were 10%, 20% and 30% NPK fertilizer weight and 10%, 20% and 30% starch concentrations. The results obtained in this study were the highest dissolving time of 3,600 seconds, while the highest percentage of the coating was 0.7519% at a concentration of 10% NPK and 30% starch coating. The conclusion is that good quality or effective biochar is found at a concentration of 10% NPK and 30% starch coating. This is influenced by the value of the analysis where, because the higher the starch concentration and the lower the NPK concentration, the dissolving time and the resulting coating percent will be higher.